Research into the processing of gold-containing technogenic waste - Khujakulov Nurmurod; Nasirova Nigora (E3S Web of Conferences)
This study investigates the processing of technogenic waste generated by the gold extraction plant at the Navoi Mining and Metallurgical Combine. The research focuses on gold-bearing technogenic waste, with its quality assessed based on the content of valuable components, additives, accompanying elements, particle size, and moisture content. The chemical and mineralogical composition, as well as the concentrations of valuable components in the waste, were determined. Various enrichment methods were applied, including flotation using different reagents and gravity separation with centrifugal concentrators and shaking tables, to process the mixed-composition technogenic waste. The optimal flotation reagent and regime for enriching gold-bearing technogenic waste were established. These findings contribute to the development of efficient processing methods for technogenic waste from gold extraction operations.